Three-year study of spinal cord injury outcomes and related secondary complications in a tertiary centre – a retrospective analysis - Joseph, Leonard H.; Ismail, Ohnmar Htwe Hj.; Naicker, Amara S.; Ying, Pua Pek; Mohammad, Abdul R. (Archives of Medical Science, 2009)
Introduction: The purpose of this study was to determine the outcomes and occurrence of secondary complications in an acute spinal cord injury (SCI) during the in-patient phase. Material and methods: The records of all patients (n = 357) admitted between June 2003 and June 2006 to the spinal ward were reviewed retrospectively. A proforma was prepared to obtain relevant information regarding demographic data, complications acquired and treatment received by the patients. Results: Of 357 patients, only 77 (58 male, 19 female) who presented with neurological deficits were included in this study. Thirty-nine percent of them were between 54 and 64 years. Motor vehicle accidents (39%) were identified to be the leading cause of SCI. Paraplegia (72.7%) was the commonest resultant outcome. In terms of outcome grading, a larger number of subjects were in ASIA D (42%) followed by ASIA C (31.2%), with only 5.2% recovered fully. Of the complications, bladder and bowel problems were the most frequent (65%), followed by spasticity (27.3%) and pressure ulcer (26%). Obviously those with tetraplegia were at higher risk for all secondary complications. Mechanical loading was effective in prevention of spasticity in around 70% of cases. The importance of breathing exercises was evident in that 80.5% did not develop pulmonary complications Although psychological problems had a lower incidence (13%), it could be due to the fact that it was under-recognized. Depressive symptoms were the predominant mode of presentation. Conclusions: This study gives us information on SCI related complications in our centre which then sets a background to look into reducing incidence of urinary problems, pressure ulcer and severity of spasticity, and also implementing and improving SCI care services.